Penciptaan Molding Rayana Henna Dengan Sumber Ide Busana Dan Aksesoris Pengantin Melayu - Endryana Putri Wahyu Purwida; Mutimmatul Faidah; Sri Usodoningtyas; Nieke Andina Wijaya (Program Studi Pendidikan Tata Rias, 2025)
Manual henna techniques which are popular in the world of bridal makeup, still have limitations in terms of technique and time efficiency, and the patterns used tend to be monotonous. One alternative to manual henna that can be developed is the use of molding as a more practical and efficient solution. This study aims to create henna molding works inspired by Melayu's bridal fashion and accessories as a form of innovation in bridal makeup art and an effort to preserve Indonesian cultural heritage. The method used is Practice-Led Research, which includes the stages of exploration, design, realization, and evaluation of the work. The design ideas were taken from the bamboo shoot and clove flower motifs on Siak songket fabric, as well as the tanjung flower from Bangka Melayu's bridal accessories. The design was created with aesthetic principles in mind and adjusted to the average size of an adult Indonesian woman's palm. The production process involved manual and digital sketching, followed by laser cutting on Oracal sticker material. The work was then packaged as a complete molding product, including complementary materials such as henna paste, glitter, and gemstones. The evaluation of the work was conducted by 33 respondents, comprising lecturers and students from the Makeup Design Program. The assessment results showed that Rayana Henna's molding work was rated very good in terms of design suitability with the source of ideas, pattern aesthetics, ease of use, and suitability as a complementary cosmetics product. Thus, Rayana Henna's molding has the potential to become an innovation in the world of bridal cosmetics as well as a means of preserving Melayu cultural heritage for the wider community. Keywords: henna molding, Melayu brides, traditional motifs, Practice-Led Research